PENERAPAN AKUNTANSI LINGKUNGAN BERDASARKAN TRIPLE BOTTOM LINE PADA RSUD H. M. DJAFAR HARUN KABUPATEN KOLAKA UTARA - Evi Nurhidayat; Asriani Junaid; Jeni Kamase (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This study aims to determine the application of environmental accounting in terms of the Triple Bottom Line concept at H. M. Djafar Harun District Hospital in North Kolaka Regency. This research uses descriptive qualitative research. Data collection uses primary and secondary data with in-depth interviews with informants who are in the area of H. M. Djafar Harun District Hospital in North Kolaka Regency. The results showed that the environmental accounting carried out by H. M. Djafar Harun District Hospital in North Kolaka Regency generally met the triple bottom line concept which included three main elements, namely profit, people and planet. Economic responsibility (profit) can be seen in health products produced from other health service activities that have been developed. Environmental responsibility (planet) can be seen from CSR programs in the environmental field that are actually carried out to save and preserve the environment such as planting trees and landfills. Social responsibility (people) is actually implemented through CSR activities in the provision of health facilities. This means that the principle of sustainable development which states that people and the environment are an integral part of the wheels of business turnover has been done by H. M. Djafar Harun District Hospital in North Kolaka Regency.